Training on the Use of the Zotero Application to Improve the Quality of Students' Academic Writing at Ma'had Al-Jami'ah, UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan - Latifah Hanum; Yona Riska Amelia; Indah Rahmadani Putri; Zulhammi Zulhammi (World Journal of Islamic Learning and Teaching, 2025)
Scientific writing is an important competency that must be mastered by students, especially in writing a thesis as a requirement for graduation at the undergraduate level. One of the problems often encountered is the weak ability of students to manage references and compile citations in accordance with academic rules. This condition has the potential to reduce the quality of scientific work and violate the principle of academic integrity. Therefore, this community service activity aims to improve students' understanding and skills in reference management through socialization of the use of the Zotero application. This activity was carried out at the Syekh Al-Hasan Ahmad Addary State Islamic University in Padangsidimpuan, involving 45 students as participants. The methods used were socialization and training, which included the delivery of conceptual material on scientific writing and citations, as well as practical assistance in using the Zotero application. The results of the activity showed that students gained a better understanding of the importance of reference management and were able to recognize the use of Zotero as a tool to systematically compile citations and bibliographies. The output of the activity was a Zotero usage guide document that can be used as a supporting reference in writing scientific papers. This activity contributes to improving students' academic and digital literacy and supports efforts to prevent plagiarism in the university environment.